The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1210/jcem-34-3-484
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Heterologous Radioimmunoassay for Human Prolactin1

Abstract: A mixed heterologous radioimmuoassay for human prolactin (HPr) has been developed in which prolactin in serum or plasma competes with radio-iodinated porcine prolactin for binding sites on anti-ovine prolactin antibody. The system is unaffected by all pituitary and placental peptides tested, and allows specific measurement of HPr in unextracted plasma or serum throughout pregnancy and in acromegaly. Sensitivity is sufficient to detect HPr in serum of normal males and females, whose mean levels ( ± SE) were 6.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
2

Year Published

1972
1972
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(21 citation statements)
references
References 20 publications
(33 reference statements)
2
17
0
2
Order By: Relevance
“…Serum thyroxine (T4) was measured by the method of Cassidy, Benotti, and Pino (16), and free thyroxine was determined by a modification of the method of Sterling and Brenner (17). Prolactin determinations were kindly performed by Dr. Lawrence Jacobs, Washington University School of Medicine (18). The radioimmunoassay for prolactin does not cross-react with other pituitary peptides nor with placental lactogen.…”
Section: Methodsmentioning
confidence: 99%
“…Serum thyroxine (T4) was measured by the method of Cassidy, Benotti, and Pino (16), and free thyroxine was determined by a modification of the method of Sterling and Brenner (17). Prolactin determinations were kindly performed by Dr. Lawrence Jacobs, Washington University School of Medicine (18). The radioimmunoassay for prolactin does not cross-react with other pituitary peptides nor with placental lactogen.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were collected at -20, 0, 15, 30, 45, and 60 min, and in most patients at 90 and 120 min. TSH, serum thyroxine, free thyroxine (T4) (16), and GH concentrations (17), and serum HPr concentrations (18,19) were measured as previously reported. No cross-reaction between TSH, HPr, or GH could be demonstrated in the assay systems.…”
Section: Methodsmentioning
confidence: 99%
“…High levels of circulating PRL during human pregnancy are well established, and were described for the first time in the early 1970s (Hwang et al 1971, Jacobs et al 1972, L'Hermite & Robyn 1972. Studies have shown that peak values reach more than five times the normal values at the 20-25th week of gestation (100-250 ng/ml; Boyar et al 1975, Ben-Jonathan et al 1996.…”
Section: Pregnancymentioning
confidence: 99%